Dietary Synbiotic Attenuated the Intestinal Inflammation in Weaned Piglets Challenged with Escherichia coli Lipopolysaccharide - Gina-Cecilia Pistol; Valeria Cristina Bulgaru; Iulian Alexandru Grosu; Daniela Eliza Marin; Georgeta Ciurescu; Gheorghe Adrian Martău; Ionelia Taranu (Animals)
At weaning, piglets deal with numerous changes and stressors, which can lead to reduced feed intake, digestive disturbances, and gut inflammation. In this context, there is a compelling need to develop new and innovative nutritional strategies aimed at restoring intestinal balance in piglets after weaning and controlling the weaning-associated intestinal inflammation. This study investigated the effect of a diet, including a synbiotic additive (a mix of grape seed and camelina meals as the prebiotic and a lactobacilli mixture as the probiotic) on intestinal inflammation in piglets after weaning. An acute inflammation was induced by the intraperitoneally challenge with Escherichia coli lipopolysaccharide (LPS). The experimental groups were as follows: Control group (piglets fed a conventional corn-soybean meal-based diet), LPS group (piglets fed the Control diet and challenged with 80 µg/b.w. of LPS), SYN group (piglets fed a basal diet, including 5% prebiotic mix and 0.1% probiotic mix, SYN diet), and SYN+LPS group (piglets fed the SYN diet and challenged with 80 µg/b.w. of LPS). Using genomic and proteomic techniques, genes and proteins related to intestinal inflammation were measured in both the jejunum and colon. The results showed that the LPS challenge induced an exacerbated inflammatory response in the jejunum and colon of piglets, inducing an overexpression of a large palette of inflammation-related mediators, including lactate dehydrogenase (LDH) activity, cytokines (e.g., interleukin (IL)—IL-1β, IL-6, tumor necrosis factor alpha—TNF-α), and chemokines (e.g., monokine induced by interferon-gamma—MIG, regulated on activation, normal T cell expressed and secreted—RANTES). All these effects are prevented by the SYN diet, which controls the amplitude of intestinal inflammation induced by the LPS challenge in piglets. Overall, these results suggested that piglets, after weaning, fed the synbiotic diet are less susceptible to the LPS challenge. This diet might be used as a nutritional strategy to alleviate intestinal inflammation in piglets after weaning.